To Determine the Frequency of Endometriosis in Sub-Fertile Women Undergoing Laparoscopy - Nazia Hassan; Rabia Jamil; Fiza Ali khan; Lubna Ali (KARACHI MEDICAL AND DENTAL COLLEGE, 2021)
It is a cross sectional study conducted in department of obs and gynae civil hospital karachi from 1 january 2016 to 30 june 2016 . There were 96 women were selected in this study . Results The average age of the women was 27.44+_3.69 years . frequency of endometriosis in subfertile women undergoing laparoscopy was found in 32(33.33%) women.